The emission surface calculation for reactive gas ion source with decreased neutral gas inleakage - Martynenko, P.A. (Вопросы атомной науки и техники, 2017)
The possibility of calculating the cathode shape of an ion sources for a beam formation system is investigated with the computer code. The acceleration of nitrogen ions with energies from 10 to 50 keV and ion currents of 10…20 mA was investigated [1]. The charged particle beams dynamic in a two-potential electron-optical system is showed. The calculation results are compared with the experimental data. The simulation can be used in the design of injection systems and selection of operating parameters of power sources of technological installations for surface modification.